SWOT and QSPM Analysis for The Implementation of Basic Processing Feasibility in Pindang Fish Quality Development in Pekalongan Regency, Central Java - Swastawati, Fronthea; Rosihun, Muhammad; Riyadi, Putut Har (Universitas Gadjah Mada, 2024)
Indonesian salted-boiled processing is a type of fish processing that is widely practiced by fish processors in the Pekalongan Regency. This fish process will produce a product known as pindang. basic processing feasibility is one of the mandatory programs that must be implemented by fish processing businesses to ensure that the products have good quality and safety. For this reason, a series of efforts are needed to encourage pindang fish processors to be able to implement this program. This study aims to identify internal and external strategic factors, create alternative strategies, and prioritize policy strategies to encourage the implementation of basic processing feasibility for pindang quality development. The research was conducted using in-depth interviews with key stakeholders with an interest in this issue. Field observations were conducted to complement the interviews that had been conducted. The SWOT and QSPM analyses were used to analyze the data. The analysis yielded six alternative strategies for carrying out the basic processing feasibility program, with the priority strategy being the optimization of assistance by fisheries extension officers.